Analisis Faktor-Faktor yang Mempengaruhi Minat Belajar Bahasa Arab Siswa MTs Ira Medan - Khairani, Beby; Ayu, Citra Sukma; Ginting, Mita Atiqah; Nasution, Sahkholid (Lembaga Intelektual Muda (LIM) Maluku, 2024)
Interest in learning plays a very important role in learning, especially Arabic. When students' interest in learning decreases in a learning process, it becomes one of the problems faced by educators, and becomes a challenge for teachers to create a learning atmosphere that is of interest to students. The purpose of this study was to analyze the factors that influence students' interest in learning at MTS Ira Medan. The method used in this study was qualitative with a descriptive approach. Data collection techniques used were interviews, observations and documentation. The results of the study showed that there were several factors that influenced students' interest in learning Arabic at MTS Ira Medan, which were divided into external and internal factors. motivation or desire to learn, students' ability to understand the material and students' attention, while external factors were the background of Arabic language education, the teacher's teaching method, the relationship between educators and students, the learning media used and the students' friendship environment at school